Is the Armenian Diaspora able to Influence the Armenian Government Over the Nagorno-Karabkh Conflict? - Huseynli, Aygun (ADA University, 2012)
The Armenian Diaspora is assessed as an influential shareholder in the current status-quo of the Nagorno-Karabakh (hereby referred to as "NK") conflict mostly due to its enormous financial means along with its political connections abroad. This argument is usually supported by the two cases in which Diaspora and Government were in opposing views regarding the NK conflict settlement in 1998 during Petrosyan' s compromising negotiations over the occupied territories of Azerbaijan, and in the recent protocols on normalization of relations with Turkey. However, the literature lacks systematic study of the funds allocated to Armenia by the Diaspora although these funds are cited as the main weight of the Diaspora over the government. In this paper I intend to study this particular discrepancy and examine whether the Armenian Diaspora's main power - in terms of its direct and indirect financial assistance to Armenia - is capable of influencing Yerevan's policy change regarding the NK conflict settlement. I measure the direct influence of the Diaspora by the volume of investments raised on projects previously implemented and currently being implemented in Armenia, as well as the Diaspora-driven foreign aids within the 2001-2011 period. The policy change is studied in the framework of systematic analysis of the messages sent out in statements of key leaders of the Armenian government on four dates related to the NK conflict and the Diaspora within the mentioned period. I used certain control variables, particularly focusing on the local and regional processes to verify the outcomes of the study. The result of these analyses confirmed that the Diaspora's financial support is slightly influential on the Armenian government's attitude in relation to the NK settlement; however, the highest correlation is observed between the control variables and the leadership's rhetoric.
Keywords: Public and International Affairs; Nagorno-Karabakh Conflict, 1988-1994.; Azerbaijan -- Relations -- Armenia (Republic); Armenia (Republic) -- Relations -- Azerbaijan.